A 5-year journey with cutis laxa in an Indian child: The de barsy syndrome revisited - Abhijit Dutta; Sudip Kumar Ghosh; Arghyaprasun Ghosh; Sutirtha Roy (Wolters Kluwer Medknow Publications, 2016)
De Barsy syndrome (DBS), synonymously known as autosomal recessive cutis laxa type III, is an extremely rare condition clinically characterized by cutis laxa, a progeroid appearance, and ophthalmologic abnormalities. We present here an account of 5-year follow-up since the birth of an Indian boy with DBS, who had a few rare and unusual manifestations. In addition, our case probably represents the first reported case of DBS from India.